RSV associated hospitalizations in children in Karachi, Pakistan: Implications for vaccine prevention strategies. Issue 7 (24th February 2017) - Ali, Asad; Yousafzai, Mohammad Tahir; Waris, Rabbia; Jafri, Fatima; Aziz, Fatima; Abbasi, Imran Naeem; Zaidi, Anita
Abstract : Major progress is being made in vaccines against Respiratory Syncytial Virus (RSV), with multiple vaccine candidates currently in the clinical phase of development. Making an investment case for public sector financing of RSV vaccine will require estimation of burden, cost‐effectiveness, and impact. The aim of this study is to determine the proportion, age distribution and clinical spectrum of RSV associated hospitalizations in children in Karachi, Pakistan. A three years prospective study was conducted at the Aga Khan University Hospital in Karachi, a city of 20 million in south Pakistan, from August 2009 to June 2012. Children less than five years old admitted with acute respiratory infections (ARI) were enrolled. Throat swabs were collected and tested for RSV using real‐time PCR. Multivariable log binomial regression analysis was performed to identify the associated factors of RSV infection. Out of 1150 children enrolled, RSV was detected among 223 (19%). Highest rate of RSV detection was in young infants less than 3 months of age (48/168, 29%), which accounted for 22% of all RSV detected. Most common diagnosis in RSV positive infants (<12 months of age) was bronchiolitis followed by pneumonia, while in older children between the ages of one and 5 years of age, pneumonia and asthma were the most common diagnosis. Although identified year‐round, RSV was most prevalent from August to October with peak in September, coinciding with the rainy season. This study identified RSV to be independently associated with younger age ( P  = 0.036), rainy season ( P  < 0.001), post‐tussive emesis ( P  = 0.008), intubation ( P  = 0.003), and discharge diagnosis of bronchiolitis ( P  = 0.004). Vaccines against RSV that target this age group are likely to yield remarkable benefit.